Application of Environmental Accounting for Company Performance - Muhamad Saddam; Sawaludin Sawaludin; Hafidz Bahar (Peneliti.net, 2022)
This research aims to see how the company’s performance will be affected by implementing environmental accounting. This research will then use a qualitative approach as the research method. The data used in this study came from various research results and previous studies still related to this research. In its analysis, this research looks at the impact given by the implementation of environmental accounting on the performance of the company. In addition to the positive effects, this study also looks at the obstacles when implementing environmental accounting. The results of this study found that an impact comes from implementing the environment for the company’s performance. The positive effect of this implementation is an increase in the company’s environmental performance, thus providing a competitive advantage and added value for the company itself. Then the implementation of environmental management accounting will also help companies to be able to maximize profitability and profits with a long-term nature and assist management in making decisions. The obstacle in implementing environmental accounting is that there is still a sense of compulsion in the application of environmental accounting because it is an obligation written in regulations that need to be obeyed. This then causes the application of environmental accounting not to be maximal.